Dalla misurazione dei servizi alla customer satisfaction - Roberto, Ventura (Firenze University Press, 2004)
Activities for the evaluation of the Florence University Library System have recently materialised in a customer satisfaction survey. The book recounts this experience and illustrates its premises, the phases of implementation, the statistical and library science methods. The survey represents the final stage of an itinerary launched through the reorganisation of the library system in 1994. From that year on, the practice of monitoring has been confirmed as an essential element of the management process. After several years devoted to the enhancement of quality, the users have been invited to express their views on the services apropos effective use and the degree of satisfaction.